Analyses of nuclearly encoded mitochondrial genes suggest gene duplication as a mechanism for resolving intralocus sexually antagonistic conflict in Drosophila. - Gallach, M.; Chandrasekaran, C.; Betrán, E. (Genome biology and evolution, 2010)
Gene duplication is probably the most important mechanism for generating new gene functions. However, gene duplication has been overlooked as a potentially effective way to resolve genetic conflicts. Here, we analyze the entire set of Drosophila melanogaster nuclearly encoded mitochondrial duplicate genes and show that both RNA- and DNA-mediated mitochondrial gene duplications exhibit an unexpectedly high rate of relocation (change in location between parental and duplicated gene) as well as an extreme tendency to avoid the X chromosome. These trends are likely related to our observation that relocated genes tend to have testis-specific expression. We also infer that these trends hold across the entire Drosophila genus. Importantly, analyses of gene ontology and functional interaction networks show that there is an overrepresentation of energy production-related functions in these mitochondrial duplicates. We discuss different hypotheses to explain our results and conclude that our findings substantiate the hypothesis that gene duplication for male germline function is likely a mechanism to resolve intralocus sexually antagonistic conflicts that we propose are common in testis. In the case of nuclearly encoded mitochondrial duplicates, our hypothesis is that past sexually antagonistic conflict related to mitochondrial energy function in Drosophila was resolved by gene duplication.